Local visitors satisfaction towards crowding at Tasik Dayang Bunting, Langkawi, Kedah - Tajuddin, Ahmad Ilham (2019)
Tasik Dayang Bunting, Langkawi is one of the main nature-based tourism and it is a very famous place for vacation to local and foreign tourist. Understanding local visitors‘ satisfaction towards crowding in Tasik Dayang Bunting is important because there were several tourists stated about the situation of crowding there. It is one of the popular tourism places, so many tourists go there and some complication on crowding happen. The first objective is to determine the perception of visitors on crowding condition in Tasik Dayang Bunting. Second objective is to examine the impact of crowding on visitor‘s satisfaction. There was only two item or place which is trail and café that measured the perception of local visitors on crowding showed the highest percentage with 46% and 44%. It can be concluded that the Tasik Dayang Bunting is not really crowded during this study was conducted. Based on the result, the local visitors TDB had very suitable and good nature-based tourism also visitors able to enjoy their trip or vacation to the TDB with this condition there.